How Will We React to the Discovery of Extraterrestrial Life? - Kwon, Jung Yul; Bercovici, Hannah L.; Cunningham, Katja; Varnum, Michael E. W. (Frontiers in Psychology, 2018)
How will humanity react to the discovery of extraterrestrial life? Speculation on this topic abounds, but empirical research is practically non-existent. We report the results of three empirical studies assessing psychological reactions to the discovery of extraterrestrial life using the Linguistic Inquiry and Word Count (LIWC) text analysis software. We examined language use in media coverage of past discovery announcements of this nature, with a focus on extraterrestrial microbial life (Pilot Study). A large online sample (N = 501) was asked to write about their own and humanity’s reaction to a hypothetical announcement of such a discovery (Study 1), and an independent, large online sample (N = 256) was asked to read and respond to a newspaper story about the claim that fossilized extraterrestrial microbial life had been found in a meteorite of Martian origin (Study 2). Across these studies, we found that reactions were significantly more positive than negative, and more reward vs. risk oriented. A mini-meta-analysis revealed large overall effect sizes (positive vs. negative affect language: g = .98; reward vs. risk language: g = .81). We also found that people’s forecasts of their own reactions showed a greater positivity bias than their forecasts of humanity’s reactions (Study 1), and that responses to reading an actual announcement of the discovery of extraterrestrial microbial life showed a greater positivity bias than responses to reading an actual announcement of the creation of man-made synthetic life (Study 2). Taken together, this work suggests that our reactions to a future confirmed discovery of microbial extraterrestrial life are likely to be fairly positive.